Infrastructures of apocalypse : American literature and the nuclear complex - Hurley, Jessica (Professor of literature) (University of Minnesota Press, 2020)
"A new approach to the vast nuclear infrastructure and the apocalypses it produces, focusing on Black, queer, Indigenous, and Asian American literatures"--